The relevance of traumato-orthopedic physiotherapy in the management of competitive swimming athletes (Research, Society and Development, 2022)
Introduction: Swimming is a sport that offers numerous benefits, however, excessive practice can be a risk to the musculoskeletal system, especially among professional swimmers. The role of trauma-orthopedic physiotherapy is to critically review the training program and learn what is expected of athletes. He should give suggestions and make recommendations for the benefit of health. The role of the physical therapist in the interdisciplinary team can contribute to a better organization of services and, consequently, better care. Objective: To investigate the relevance of trauma-orthopedic physical therapy in swimming athletes. Methods: This is an integrative literature review. The bibliographic survey took place during the month of June 2022 in the following databases: LILACS, MEDLINE and SciELO. We used combinations of descriptors in Portuguese, English and Spanish: “Physiotherapy”, “Athletes” and “Swimming”. Results: From the literature review and analysis of articles, seven were selected and composed the final version of this study. Based on the data exposed in the research, we can see that the physiotherapy professional proves to be indispensable for swimming athletes both at a competitive level and at an amateur level. Conclusion: Physiotherapy is essential within the interdisciplinary team that provides services to swimming athletes, as the performance is present in all spheres of care as in epidemiological surveillance evaluating possible injuries, preventive therapeutic approaches, prescriptions and adaptations of physical activities, rehabilitation and general guidelines. Thus maintaining longevity in practice.